HORMONE REPLACEMENT THERAPY WITH ESTROGEN AND PROGESTOGEN: IMPACT ON WEIGHT AND FAT DISTRIBUTION IN PERI-MENOPAUSAL AND POST-MENOPAUSAL WOMEN - Dr. Kalsum Khan; Dr. Alveena Khan; Dr. Aqsa Arbab Khan; Dr. Reema Gul; Dr. Maria Ali Shah; Dr. Jahangir Zaib (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Hormone replacement therapy (HRT) is commonly used to manage menopausal symptoms and prevent bone loss in post-menopausal women. This study evaluates the effects of ‘unopposed estrogen and combined estrogen with progestogen HRT on body weight and fat distribution in peri-menopausal and post-menopausal women’. ‘To assess whether these HRT regimens influence body weight, BMI, waist-to-hip ratio, fat mass, and skinfold thickness’ compared to non-HRT users over six months.Methods: A randomized controlled trial was conducted with 150 women aged 45 or older at Poonch Medical College and its affiliated Hospital (AJK). Participants were assigned to receive ‘unopposed estrogen HRT, combined estrogen and progestogen HRT’ or no HRT (control). Assessments included baseline and six-month measurements of body composition. Statistical analysis used ANOVA and chi-square tests.Results: Demographics were similar across groups at baseline. There were no significant differences in weight change, BMI change, ‘waist-to-hip ratio change, fat mass change, or skinfold thickness change between HRT groups and controls (p > 0.05).Conclusion: Six months of ‘unopposed estrogen or combined estrogen and progestogen HRT did not significantly alter body weight or fat distribution in peri-menopausal and post-menopausal women’. These findings suggest that concerns about substantial weight gain with HRT may be unfounded in the short term. Further research with larger cohorts and longer follow-ups is needed to confirm these results and explore broader health impacts in menopausal women.